MODIFIKASI PENGUNCI KEPALA LEPAS UNTUK MESIN BUBUT MAXIMAT V13 - Intan Rahma Yuni; Arif Rahman; Elvis Adril; Yuli Yetri (Politeknik Negeri Batam, 2020)
During this time the tailstock off which is commonly used is made of castings which is difficult to obtain and the price is quite expensive, and it becomes on obstacle to replace it if there is damage or loss of locking the “tailstock”. For modifying it can be done in order to facilitate the use of machine, which is the modification of the tailstock release on the lathe because the design was previously damage and cannot be used properly and also makes locking more efficient and better than before. With the right material selection and material calculation, the desired target will be achieved perfectly and the use will ber very helpful in the use of loose heads on the lathe.